Prise en charge et prévention des violences sexuelles à Abidjan : entre stigmatisation et inégalités - Nassoua Antoine Okpo; Michel Koudou Gbagbo; Baleta Lynda Carole Dalli (Rivista di Criminologia, Vittimologia e Sicurezza)
This study aims to analyze the barriers to care and prevention of sexual violence against women in Abidjan, hypothesizing that socio-economic, cultural, and institutional factors limit the effectiveness of current measures. Using a qualitative methodology, based on the analysis of archives from five local associations specialized in victim support, the study draws on the theory of structural violence to highlight the power dynamics at play. The results reveal that situational prevention, though promising, is not sufficiently integrated into public policies. The study suggests ways to improve coordination between institutional actors and associations to strengthen prevention and victim support measures.